Avaliação de risco ambiental de ambientes aquáticos afetados pelo uso de agrotóxicos - Rebelo, Rafaela Maciel (2014)
Ecological risk assessment is a process evaluating the likelihood that adverse ecological effects may occur or are occurring as a result of exposure to one or more substances. Relevant information needed to predict risks from pesticides includes their physical chemical properties, mobility in soil, persistence in the environment, and bioaccumulation and toxicity in relevant organisms. Although currently a requirement for pesticide registration in Brazil, this process is not yet fully implemented in the country. This review aims to outline the principles of environmental risk assessment for pesticides, focusing on aquatic organisms, and to discuss the studies and efforts conducted in Brazil in this area.